Levi-Strauss and the Opera - Vlado Kotnik (University of Belgrade, 2016)
This paper is dedicated to Claude Levi-Strauss and his structural reading of opera as metaphorical ‘composing’ of an anthropological grand opera, materialized in the four-volume study of Mythologiques, which refers to Wagner’s tetralogy of The Ring. He created a type of comparative view of the function and structure of myth schemes in Amerindian culture and the orchestral scores of Wagner’s operas, and implicitly signalled that European music, with its eminent representation – opera – has had the same value or similar symbolic position in the mind and life of a contemporary European that myth has had in ‘the savage mind’. Through this, he can lead us to the understanding of opera as myth and metaphor. However, the paper extends the discussion on Levi-Strauss to a broader historical picture of the relationship between opera and mythology as two symbolic systems of European culture.